ETHICAL CHALLENGES OF CIVIL SERVICES IN BOSNIA AND HERZEGOVINA - Vranjes, Nevenko D. (Politeia, 2026)
Civil service ethics today represents a legally and sub-legally regulated category. This implies that conscience, ethics, honesty, and other moral categories are increasingly less identified as implied social values, necessitating their prescription and sanctioning through legal norms. Factors most influencing unethical behavior of civil servants in Bosnia and Herzegovina can be grouped into several categories: politicization of the civil service (selection process not based on meritocracy principles), the broad scope of the civil service (excessive number of civil servants at all levels of administrative organization who exhibit low civil service culture and lack training), high corruption index in society (where civil servants act as both subjects and objects of corrupt activities), weak prevention and penalization of ethical rule violations, difficulty in proving mobbing and discrimination in the civil service with inadequate response from responsible authorities to prevent and punish these phenomena, and weak prevention and management of conflicts of interest in general and in the civil service. Additionally, political instability and limited resources of civil service agencies hinder meritocracy, thus requiring interventions such as mandatory annual ethics training and testing; a digital platform for reporting conflicts of interest; and strengthening sanctions for executives who generate unethical behavior.